The Role of Changing Housing Policies in Housing Affordability and Accessibility in Developing Countries: The Case of Kenya. - Collins Ouma Agayi; Özer Karakayacı (Journal of Contemporary Urban Affairs, 2020)
Rapid urbanization has led to the influx of people into urban areas as people seek better life opportunities. This migration has however largely not been planned, resulting in population explosions in the cities. Relying on existing research on the topic and government reports, this study finds that many middle and low-income families in Kenya have ended up living in informal settlements in urban areas due to housing unaffordability. The study further determines that the problem of housing is more pronounced in developing countries. Studies related to this issue establish that the housing crisis cannot only be attributed to rural-urban migration but also other factors like failed housing policies, poor housing financial systems, too much interference in the running of housing by the government and complex land tenure systems among others. This research, therefore, identifies the critical housing crisis issues, housing policy gaps in Kenya and proposes policy actions and the potential role of governments in a housing market to address affordability challenges. The study establishes the role of government and other institutions in the housing sector and proposes land and housing reforms that can add knowledge to future research in similar areas.